Retail display case merchandisings consist and price-elasticity of demand for U.S. beef and pork variety meats sold in Mexican grocery stores - Huerta-Leidenz, Nelson; Valdez-Muñoz, Alejandra; Lopez, Fernando; Howard, Scott T; Cheyenne, Dixon; E. Belk, Keith (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2017)
Mexico imports large volumes of US red meats (products) and edible coproducts (variety meats, VM), but little is known about the distribution and fresh marketing of these VM. To quantify the offering and qualify the influence of location and socioeconomic status of clientele on the presence of VM in the retail case, supermarkets and other stores known to regularly merchandise US products were surveyed in five cities (Mexico City, Monterrey, Guadalajara, Queretaro, Leon, and Guanajuato) of the three most populous regions (Central, Northern and Mid-Western) of Mexico. Frequency of US meat and co-products in retail store display cases were determined by product type and species (bovine or porcine) relative to total products displayed (i.e., the total number of packets sampled on shelves, N= 1535), and the association with location of the store (city), and socioeconomic status (level) of the clientele. For complementing the information collected in the stores, the coefficient of elasticity of demand (E ) was estimated. The total proportion of VM in the visited stores ( 11%) was not affected by the level of their clientele (P>0.05). Retail stores in Guadalajara were the more likely to market VM (P<0.05). Elasticity of demand (E p p ) estimates supported cultural preference for porcine VM, independent of the price of meat of this species (E<1). Several U.S. VM with a history of massive exportation to Mexico (e.g., liver) were scarce or not found in the retail outlets visited, demonstrating the importance of local wet markets in Mexico to channel their supply.